2010
DOI: 10.1007/s00277-010-1115-x
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of intron 22-related rearrangements of F8 by inverse-shifting PCR in Egyptian hemophilia A patients

Abstract: Hemophilia A (HA) is the most common severe bleeding disorder in humans, affecting one in 5,000 male births. In severe HA, intron 22 inversion of F8 is the most prevalent mutation, accounting for 40-50% of all mutations; however, little is known about the disease-causing mutations among Egyptian hemophiliacs. We aimed at genotyping all possible known DNA rearrangements of intron 22 of F8 in Egyptian HA patients. Peripheral blood samples were collected from 30 Egyptian HA patients (13 severe, ten moderate, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 29 publications
5
18
0
1
Order By: Relevance
“…The same tendency was found for the intron 1 inversion, which is reported with a frequency of 5% [10]. When we compare our findings with previous data from other Arab countries the frequencies of these 2 inversions are lower in our patients [11-14]. This result shows that our patients have a specific genetic profile which is confirmed by other molecular studies concerning our country [15].…”
Section: Discussionsupporting
confidence: 91%
“…The same tendency was found for the intron 1 inversion, which is reported with a frequency of 5% [10]. When we compare our findings with previous data from other Arab countries the frequencies of these 2 inversions are lower in our patients [11-14]. This result shows that our patients have a specific genetic profile which is confirmed by other molecular studies concerning our country [15].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings confirm those of previous studies. The frequency of Inv 22 in our study was 44 %, which is similar to that in populations studied in the United Kingdom [13], Spain [17], Italy [18], Argentina [19,20], India [21], Egypt [22], Iran [23], Mexico [24], Hungary [15], and Costa Rica [25]. On the basis of these results, we concluded that the incidence in different populations is similar.…”
Section: Discussionsupporting
confidence: 74%
“…IS-PCR avoids PCR amplification through long and GC rich sequences of F8 gene duplicons associated with intron 22h and intron 1h that these sequences may be amplified in LD-PCR 18,21 . Recently, IS-PCR method has been developed 18 and applied for the detection of int 22 inversion in different studies 25,26 . In this study we used IS-PCR assay to evaluate the presence of int 22 and int 1 inversion in severe HA patients from a single centre in Isfahan, Iran.…”
Section: Discussionmentioning
confidence: 99%